Effect of electronic coupling on the electrocatalytic performance of platinum metal. Issue 84 (26th August 2016) - Feng, Yan; Wang, Caixia; Ye, Feng; Liu, Hui; Yang, Jun
Abstract : The relationship between the electronic coupling effect and electrocatalytic property of platinum metal was investigated through a core–shell construction. Abstract : Engineering the electronic coupling in platinum-based heterogeneous nanomaterials is an effective way to enhance their activity in electrocatalysis. Herein, we study the relationship between the electronic coupling and electrocatalytic activity of Pt metal through a core–shell construction. We prepare core–shell Ag–Pt, Au–Pt, and hollow Pt nanoparticles with comparable sizes and morphologies, and tailor the electron density around the Pt atoms via the differences in electronegativities between the core and shell components. Specifically, core–shell Ag–Pt nanoparticles are active for the methanol oxidation reaction due to the presence of electron donation from Ag to Pt, while core–shell Au–Pt nanoparticles exhibit superior activity for the oxygen reduction reaction due to the electron withdrawing effect from Pt by Au. The bimetallic core–shell particles therefore have the feasibility of tuning a Pt surface for two very different structure sensitive catalytic reactions, and further enhancement in electrocatalysis might be achieved by optimizing both the core size and shell thickness in the core–shell materials.